Seasonal variation in hospitalizations for peptic ulcer disease: A five-year retrospective study from Latvia - Abdulrahman Al-Dawoudi; Mujahed Dalain; Daniil Varlamov; Nazar Kopytko; Davis Freimanis (PLoS ONE, 2026)
Peptic ulcer disease (PUD) remains a significant global health burden, yet data on seasonal variations in PUD hospitalizations are inconsistent across regions. No studies have assessed seasonal patterns in PUD hospitalizations in Latvia or the broader Baltic region. This study aimed to evaluate whether seasonal factors influence PUD hospitalizations in this temperate-climate setting. We conducted a retrospective cohort study of adult hospitalizations with a primary discharge diagnosis of PUD (ICD-10 codes K25–K28) from 2020 to 2024 at a tertiary care hospital in Riga, Latvia. Seasonal distribution, ulcer subtype, bleeding status, length of stay (LOS), and in-hospital mortality were analyzed using chi-square, Mann–Whitney U, and Kruskal–Wallis tests, as appropriate. Multivariable logistic regression was performed to assess independent predictors of in-hospital mortality. A total of 606 hospitalizations were analyzed (median age: 66 years; 59.1% male). The median LOS was 6 days. Older adults (≥65 years) had higher in-hospital mortality compared with those <65 years (11.7% vs. 3.5%, representing an absolute difference of 8.2%). Seasonal distribution was relatively even: 22.4% in winter, 23.4% in spring, 30.4% in summer, and 23.8% in fall, with a maximum absolute difference of 8.0% between peak and trough seasons; no significant seasonal differences were observed in demographic or clinical characteristics. In multivariable analysis, season was not independently associated with in-hospital mortality (overall Wald p = 0.952), whereas increasing age was independently associated with mortality (adjusted odds ratio [aOR] 1.04 per year; 95% CI 1.02–1.07; p < 0.001). This study provides the first regional evidence from the Baltic area suggesting that seasonal climatic variation does not substantially influence severe PUD hospitalization patterns within a centralized European healthcare system.